Spatial planning, metropolitan governance and territorial politics in Europe: Dublin as a case of metro-phobia?. (October 2019) - Moore-Cherry, Niamh; Tomaney, John
The growing concentration of production and population in capital cities in Europe is accompanied by metropolitan governance reform with two policy objectives in mind. Firstly, capital cities are promoted as 'national champions' in the context of global territorial competition. Secondly, metropolitan regions are characterised by recurrent crises of 'governability' as economic, social, environmental and infrastructural interdependencies escape existing jurisdictional scales. However, this process is highly uneven, reflecting the ways in which cities are embedded in their national contexts. Drawing from the literature on varieties of capitalism, and in particular O'Riain's perspective on the Irish case, we suggest that in an era when cities are claimed to be acting as 'national champions', territorial politics need to be more strongly foregrounded in these discussions. Through an in-depth qualitative case-study of Dublin (Ireland), we argue that while government power may be strongly centralised in the city of Dublin, the spatial entity of Dublin is relatively powerless. Despite a number of recommendations since the 1970s, there has been little will or action to meaningfully devolve power to the city-regional level in any way, contrary to comparative European experiences. The paper illustrates how a central state stranglehold over the Dublin metropolitan area is hampering the efficient governance and sustainable development of the city. These governance constraints at the sub-national level with significant planning implications indicate a reluctance to engage with the metropolitan as a particular territorial scale in Ireland – and a profound fixity in the architecture of the state. We term this metro-phobia .